Basic professional skills of the General Comprehensive Doctor: A methodological assessment approach in Cienfuegos. - María Aurelia San Juan Bosch (Medisur)
The assessment process of medical competences of General Comprehensive Doctors is a core element to determine their needs and their competence level. It is an important constituent for the continue improvement of this kind of professional. The development of Human Resources of the Health Sector is one of the main premises to achieve a better quality of sanitary assistance. The subject of continuous preparation of human resources in Primary Health Care is presently a high priority challenge of National Health Sector. The scientific and human quality of our workers is the foundation of our achievements in this sector. This work highlights the necessity for a methodology to assess the basic professional competences of General Comprehensive Doctors and its field is limited to the assessment of professional competences of these doctors to guarantee quality in our services. The newness of this proposal lies on the option of a theoretical systematic treatment of a methodology for the assessment of professional competences of these doctors, with a holistic approach linking theory to practice and thus, contrasting expected and achieved goals.